2019
DOI: 10.1186/s12957-019-1765-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of adrenal lesions larger than 5 cm in diameter (an analysis of 251 cases)

Abstract: BackgroundTo describe the pathological distribution, imaging manifestations, and surgical managements and prognosis of large adrenal tumors (LATs) ≥ 5 cmMethodsA total of 251 patients with LATs were analyzed on the basis of pathological or clinical diagnosis. Regarding surgery, open adrenalectomy was performed on 89 patients, and laparoscopic adrenalectomy was performed on 89 patients. Thirty-two patients with bilateral tumors were analyzed in terms of clinical characteristics. The survival rate was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…In our study, lobular type and irregular type were associated with IHD with regard to tumor shape. The present analyses showed that round type was frequently found in pheochromocytomas ( 9 , 12 ). To the best of our knowledge, the shape of lesions was not adopted into reports on risk factors of IHD in patients with pheochromocytoma.…”
Section: Discussionsupporting
confidence: 58%
“…In our study, lobular type and irregular type were associated with IHD with regard to tumor shape. The present analyses showed that round type was frequently found in pheochromocytomas ( 9 , 12 ). To the best of our knowledge, the shape of lesions was not adopted into reports on risk factors of IHD in patients with pheochromocytoma.…”
Section: Discussionsupporting
confidence: 58%
“…With the development of diagnostic imaging, the number of adrenal tumors found by chance is increasing [ 24 , 25 ]. Among adrenal lesions larger than 5 cm in diameter on CT, 28.69% are malignant adrenal tumors, including adrenal lymphoma, accounting for 1.20% of all cases [ 26 ]; however, CT findings of primary adrenal lymphoma are not specific. Rashidi et al have reported that in CT studies of primary adrenal lymphomas, the frequency of homogeneous and heterogeneous appearing masses is similar; most masses are hypodense, whereas some are hyperdense; and most enhancement patterns are “slight to moderate enhancement,” whereas some are “no or poor enhancement [ 27 ].” Therefore, a definitive diagnosis is only established by resection or biopsy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data about adrenal tumors homogeneity/ heterogeneity is very limited. In one series of 117 lesions above 5 cm, ACA's were homogenous only in 55%, ganglioneuroma's in 85%, PHEO's in 2%, ACC in 2%, and metastases in 1% [5]. Such high percentage of heterogeneity seen in large ACA's may be a result of local intra-tumoral bleeding in growing lesion and secondary calcifications.…”
Section: Introductionmentioning
confidence: 98%
“…Pheochromocytomas (PHEOs), adrenocortical cancer (ACC), and metastases account for 7%, 5%, and 8% respectively [4]. Large adrenal tumors (LAT's) defined as more than 4-6 cm are rare, with the incidence from 8.6-38.6% of adrenal tumors [5]. Although the risk of malignancy clearly correlates with the size of a lesion, tumor size of more than 4 cm represents only 31-61% specificity for the diagnosis of malignant tumor [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation